2021
DOI: 10.1097/coc.0000000000000796
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported Quality of Life After SBRT, LDR, and HDR Brachytherapy for Prostate Cancer

Abstract: Purpose: We sought to compare changes in patient-reported quality of life (PRQOL) following stereotactic body radiation therapy (SBRT), high dose rate (HDR), and low dose rate (LDR) brachytherapy for prostate cancer.Materials and Methods: International Prostate Symptom Score (IPSS), Sexual Health Inventory For Men (SHIM), and Expanded Prostate cancer Index Composite Short Form (EPIC-26) were prospectively collected for men with low/intermediate-risk cancer treated at a single institution. We used Generalized E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
2
4
0
Order By: Relevance
“…Reassuringly, regardless of baseline urinary function scores, all men who had either LDR-BT or HDR-BT monotherapy in Victoria had excellent urinary function domain score 12month post-treatment, comparable to multiple earlier series on LDR-BT 18,19 or HDR-BT. [20][21][22] The urinary function scores at 12 months after LDR-BT or HDR-BT monotherapy in this study were also comparable to men who had external beam radiation therapy with BT boost in previous PCOR-Vic study 23 (Table 4). On the other hand, it is unknown whether men who had LDR-BT and HDR-BT had comparable baseline sexual function score, 24 given that pre-treatment sexual (dys)function is generally not a selection or exclusion criteria for LDR-BT or HDR-BT.…”
Section: Discussionsupporting
confidence: 63%
“…Reassuringly, regardless of baseline urinary function scores, all men who had either LDR-BT or HDR-BT monotherapy in Victoria had excellent urinary function domain score 12month post-treatment, comparable to multiple earlier series on LDR-BT 18,19 or HDR-BT. [20][21][22] The urinary function scores at 12 months after LDR-BT or HDR-BT monotherapy in this study were also comparable to men who had external beam radiation therapy with BT boost in previous PCOR-Vic study 23 (Table 4). On the other hand, it is unknown whether men who had LDR-BT and HDR-BT had comparable baseline sexual function score, 24 given that pre-treatment sexual (dys)function is generally not a selection or exclusion criteria for LDR-BT or HDR-BT.…”
Section: Discussionsupporting
confidence: 63%
“…1,2 Low-dose-rate (LDR) prostate brachytherapy (BT-'short distance' therapy in Greek) is one of the most effective methods for the treatment of prostate cancer. 3 Among the available therapeutic modalities, needle insertion (a minimally invasive procedure for biopsy, drug delivery, and ablation) is commonly used because it offers low trauma, fast recovery and high efficacy. 1 LDR-BT involves loading a needle with rice-sized radioactive seeds for insertion into the prostate.…”
Section: Introduction 1| Needle-based Soft Tissue Interventionmentioning
confidence: 99%
“…(3) the pubic arch does not obstruct the needle insertion route. 3 As such, TR prostate BT was used in this study.…”
Section: Introduction 1| Needle-based Soft Tissue Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prostate cancer has a low α/β ratio value that favors the use of hypofractionated radiotherapy schedules [3]. Multiple clinical trials have demonstrated that stereotactic body radiation therapy (SBRT) using doses of 7.5-9 Gy per fraction, for a total of five fractions, is safe and likely non-inferior to conventionally fractionated RT regimens [4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%